KEDARURATAN (AL-MADLARAT) SEBAGAI LANDASAN PERUBAHAN PERUNDANG-UNDANGAN DAN HUKUM ISLAM DI INDONESIA PADA ERA PANDEMI - Panjalu, Gandhung Fajar (Muhammadiyah University of Surabaya, 2021)
Establishing a statutory regulation as a guide in acting is one of the things that the government needs to do, this is also used as a form of government effort in the welfare of its people. However, it can be seen that the current condition where almost all countries including Indonesia have been hit by the Covid-19 outbreak, which means that the situation or situation of the community is not same like before pandemic era. Covid-19 is an infectious disease where the cause of this disease comes from Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2), or a type of coronavirus that was recently discovered. Covid-19 is now designated as a pandemic, where many cases have occurred all over the world. With this pandemi, it certainly has an impact on various fields of life, one of which is the law. Therefore, the flexibility of the law is questioned considering the current condition of Indonesian society is not the same. The purpose of this paper is to answer the formulation of the problem, to describe out the emergencial condition as a basic of the change of the legislation and islamic law in Indonesia during the Covid-19 pandemic.